Judicial Challenges in Prosecuting Cross-Border Cyber Crimes (International Journal of Criminology & Justice, 2025)
Cybercrime has emerged as a serious global threat, and international cases are among the most challenging in terms of law and institutions. Bangladesh, as one of the fastest-growing digital frontiers, faces an increasing number of cyber threats undermining, especially its ICT Act (2006) and Digital Security Act (2018). Old laws, global cooperation failures, and poor forensic abilities present obstacles to successful conviction. The study aims to explore the judicial impediments, the jurisdictional problem, inadequacy of national law, international assistance, and the technical evidence in the context of prosecuting the cybercrimes perpetrated across the border in Bangladesh. The study is quantitative in nature, with a sample size of 400, consisting of ICT practitioners, lawyers, security personnel, and policy makers. Descriptive statistics were computed to examine professional perspectives and to establish any patterns. Findings revealed that outdated laws, unclear jurisdictions, and a lack of extradition agreements provide loopholes for cybercriminals. They also stressed that other contributing factors include lack of international cooperation, unsuccessful implementation of Mutual Legal Assistance Treaties (MLATs), and an inadequate forensic toolkit. Shortage of skills among research staff also undermines the handling and prosecution of evidence. The research indicates a pressing requirement for the reform of law, creation of specialized cyber courts, improved forensic infrastructure, and enhanced international cooperation to enable Bangladesh to combat transnational cybercrimes effectively.